Screening for Susceptibility-Related Biomarkers of Diclofenac-Induced Liver Injury in Rats Using Metabolomics - Tu, Can; Gao, Yuan; Song, Di; Niu, Ming; Ma, Run-ran; Zhou, Ming-xi; He, Xian; Xiao, Xiao-he; Wang, Jia-bo (Frontiers in Pharmacology, 2021)
Early identifying susceptible individuals of IDILI is an unmet challenging demand. Diclofenac (Dicl), one of the most widely popular over-the-counter drugs in pain management worldwide, may induce not only liver dysfunction but also acute liver failure, even death. In article, we observed that Dicl-related hepatobiliary adverse reactions more frequently occurred in cases with immune activation. We further found divert hepatotoxicity responses in individual when exposing to Dicl and modest inflammation potentiated Dicl-induced liver injury in rats. Moreover, we found that those susceptible individuals have unique metabolomic characteristics in rat plasma by metabolomics approach, which can be used to distinguish susceptible individuals from unsusceptible ones. The 23 identified susceptibility-related metabolites were enriched to several metabolic pathways related to acute phase reactions of immunocytes and inflammatory responses, including sphingolipid, tyrosine, phenylalanine, tryptophan, lipid metabolism pathways, which implies the mechanistic role of metabolic and immune disturbance in affecting the susceptibility of Dicl-IDILI. We further identified 9 metabolite biomarkers with potent diagnostic capabilities to distinguish susceptible individuals from unsusceptible ones by using receiver operating characteristic (ROC) curve. These findings elucidated the potential utility of metabolomic biomarkers to identify susceptible individuals of a hepatotoxic drug and the underlying mechanism of metabolic and immune disturbance in occurrence of IDILI.